Research on numerical simulation method for degradation of whole-train wheels of EMU in full-process O&M - CHEN Boqing; ZENG Yuanchen; SONG Dongli; ZHANG Weihua; FU Shuangbo; JIANG Chen (机车电传动)
Wheels are the key components of EMU and degradation occurs on wheels after long-term service, impeding the operation safety and stability of EMU. In addition, the wheels of the entire train of EMU are operated and maintained in groups, so the degradation of each wheel has overall synchronization and individual differences, and adjacent wheels affect each other in the operation and maintenance (O&M) processes. Wheel degradation is characterized by diverse influencing factors, mutual influence of parameters and high randomness, so a numerical simulation method was proposed for the degradation of whole-train wheels of EMU in full-process O&M. A probabilistic model that incorporated the relevant factors, degradation laws and uncertainties is used to simulate the key factors in the operation and maintenance process, such as wheel wear, defects and reprofiling, and then the numerical simulation of the wheel degradation process was realized through closed-loop iteration. Then, a numerical simulation method of wheel degradation based on Monte Carlo simulation is proposed to simulate the degradation process of whole-train wheels of EMU under the influence in random links. Finally, based on the operation and maintenance data of EMU in China, modeling and simulation examples were given. The results show that the method can effectively predict the average level and uncertainties of degradation of whole-train wheels of EMU, enabling forecast of the remaining service life of wheels. The method can also be used to optimize of the overhaul limits of wheels based on the wheel operation and maintenance cost evaluation, so as to reduce the cost in the whole process of wheel operation and maintenance and improve the economy of EMU maintenance.